Clinical profi ling of patients with peripartum cardiomyopathy and its value for translational research - Forster, Olaf; Sliwa, Karen; Hilfi ker-Kleiner, Denise (SA Heart Journal, 2017)
Postpartum cardiomyopathy (PPCM) is a disease of unknown etiology and exposes women to high risk of mortality after delivery despite optimal medical therapy. Experimental data suggested that enhanced oxidative stress promotes the proteolytical processing of the lactation hormone prolactin into a biologically active derivative, the 16kDa prolactin, which appears to be a major cause for PPCM. We observed increased oxLDL levels in a subset of these PPCM patients, indicative of oxidative stress, enhanced Cathepsin D activity and substantial levels of the cleaved 16kDa form of prolactin. We therefore propose that the excessive generation of 16kDa prolactin mediates PPCM in humans and suggest that inhibition of prolactin release may represent a novel therapeutic strategy for PPCM.